SURGICAL TREATMENT OF CHILDREN WITH AXIAL DEFORMITIES OF THE LOWER EXTREMITIES - Babajanov, D.E.; Djuraev, A.M.; Rakhmatullaev, H.R. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Objective: To improve the results of treatment of children with axial deformities of the lower extremities by determining indications for various types of operations depending on their etiology, severity and age of the patient. Material and methods: Under observation, there were 152 children with various deformations of the axis of the lower extremities on the basis of congenital and acquired diseases of the musculoskeletal system, including 54 (35.5%) boys and 98 (64.5%) girls, under the age of 4 years - 42, from 4 to 7 years - 62, from 7 to 10 years - 21, 11 years and older - 27. Results: Surgical treatment was applied in 71 children. To eliminate axial deformations in patients, apparatus-surgical methods and temporary hemi-epiphysioseodes were used. Temporary hemiepiphysioseodes proved to be effective for mild degrees of deformation. All patients received excellent and good results. Conclusions: Temporary hemiepiphysioseodesis to eliminate rickets of lower limbs in children is a more minimally invasive method than various osteotomies.